The Toxic Effects of Formaldehyde on the Nervous System - Songur, Ahmet; Ozen, Oguz Aslan; Sarsilmaz, Mustafa (Springer, 2010)
[Abstract Not Available]
Keywords: Essential Fatty-Acids; Inhaled Formaldehyde; Rat Hippocampus; Dentate Gyrus; Iron Concentrations; Exposure Databases; Cerebral-Ischemia; Prefrontal Cortex; Risk Assessment; Cell Number